1997
DOI: 10.1074/jbc.272.44.28050
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Strain Increases Expression of the Brain Natriuretic Peptide Gene in Rat Cardiac Myocytes

Abstract: Using a device that applies cyclical strain (1 Hz) to ventricular cardiocytes cultured on collagen-coated silicone elastomer surfaces, we have demonstrated straindependent increases in brain natriuretic peptide (BNP) secretion, BNP mRNA levels, and expression of a transiently transfected ؊1595 human BNP-luciferase reporter. When actinomycin D (10 M) was introduced concomitantly with the strain stimulus, the strain-induced increase in BNP mRNA was eliminated, and the decay of transcripts was identical in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
69
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 52 publications
1
69
0
Order By: Relevance
“…The activation of both p38 MAPK 12 and ERK 7,8,10 has been demonstrated after the application of mechanical strain to cultured myocytes. The involvement of these pathways extends to both the ET-dependent and -independent components of the strain response (see earlier).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The activation of both p38 MAPK 12 and ERK 7,8,10 has been demonstrated after the application of mechanical strain to cultured myocytes. The involvement of these pathways extends to both the ET-dependent and -independent components of the strain response (see earlier).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the signaling mechanism or mechanisms that account for this activity remains undefined, although the JNKs represent obvious candidates. Both ET 3 and mechanical strain 9,10 have been shown to stimulate JNK activity in cultured cardiac myocytes, and this stimulation has been linked to the hypertrophic phenotype. The levels of inhibition cited probably are low estimates of the true participation of this pathway (or pathways) in signaling the response to mechanical strain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that NT-proBNP was potentially useful as a biomarker in Fabry disease and correlated with changes in Mainz Severity Score Index (Torralba-Cabeza et al 2011). BNP gene expression is stimulated by both mechanical strain (Liang et al 1997;Liang and Gardner 1998) and autocrine/paracrine processes via angiotensin II (Liang and Gardner 1998). Renin-angiotensin system blockade reduces plasma NT-proBNP level and improves prognosis, which is most likely a reflection of improved cardiac function due to the treatment (Anand et al 2003).…”
Section: Discussionmentioning
confidence: 99%